2021
DOI: 10.1371/journal.pone.0259908
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the SARS-CoV-2 positivity ratio and upper respiratory tract viral load among asymptomatic individuals screened before hospitalization or surgery in Flanders, Belgium

Abstract: Introduction The incidence of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infections in the Belgian community is mainly estimated based on test results of patients with coronavirus disease (COVID-19)-like symptoms. The aim of this study was to investigate the evolution of the SARS-CoV-2 reverse transcriptase polymerase chain reaction (RT-PCR) positivity ratio and distribution of viral loads within a cohort of asymptomatic patients screened prior hospitalization or surgery, stratified by age ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Another limitation of the hospital screening data is the relatively low fraction of the population tested in this framework, leading to more uncertainty, especially for younger age groups. Heireman et al [ 20 ] also used PR of screening tests performed on the occasion of non-COVID-19-related hospital admission in Belgium to assess the SARS-CoV-2 circulation among patients without COVID-19 symptoms during the autumn wave of 2020. Among other findings, they observed that the peak of PR considering all tests occurred one month before the peak of PR considering only pre-hospitalization screening tests (October instead of November 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation of the hospital screening data is the relatively low fraction of the population tested in this framework, leading to more uncertainty, especially for younger age groups. Heireman et al [ 20 ] also used PR of screening tests performed on the occasion of non-COVID-19-related hospital admission in Belgium to assess the SARS-CoV-2 circulation among patients without COVID-19 symptoms during the autumn wave of 2020. Among other findings, they observed that the peak of PR considering all tests occurred one month before the peak of PR considering only pre-hospitalization screening tests (October instead of November 2020).…”
Section: Discussionmentioning
confidence: 99%